2019
DOI: 10.1002/pon.5148
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to enhance self‐efficacy in cancer patients: A meta‐analysis of randomized controlled trials

Abstract: Objective: Self-efficacy expectations are associated with improvements in problematic outcomes widely considered clinically significant (ie, emotional distress, fatigue, and pain), related to positive health behaviors, and as a type of personal agency, inherently valuable. Self-efficacy expectancies, estimates of confidence to execute behaviors, are important in that changes in self-efficacy expectations are positively related to future behaviors that promote health and well-being. The current meta-analysis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 59 publications
1
61
0
11
Order By: Relevance
“…Based on our findings, resources need to be allocated to alleviating survivors' excessive concerns and facilitating their self‐efficacy for coping in order to improve QOL. For example, cognitive–behavioral therapy has shown promise for reducing cancer survivors' concerns and improving self‐efficacy 37,38 . In addition, healthcare providers may devote more time to inquiring about survivors' concerns and addressing these concerns through responsive and supportive communication.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, resources need to be allocated to alleviating survivors' excessive concerns and facilitating their self‐efficacy for coping in order to improve QOL. For example, cognitive–behavioral therapy has shown promise for reducing cancer survivors' concerns and improving self‐efficacy 37,38 . In addition, healthcare providers may devote more time to inquiring about survivors' concerns and addressing these concerns through responsive and supportive communication.…”
Section: Discussionmentioning
confidence: 99%
“…pain, physical activity, coping with cancer and stress management). This study also revealed a small/medium effect size of physical activity on cancer patients’ SE (Merluzzi et al., 2019).…”
Section: Interventionsmentioning
confidence: 58%
“…To evaluate the effectiveness of interventions aimed at increasing RTW-SE and promote RTW in cancer patients, randomised controlled trials should be conducted. For example, a meta-analysis conducted by Merluzzi et al (2019) revealed medium effect sizes of complementary/integrative medicine, social support, cognitive behaviour therapy and self-management interventions in enhancing cancer patients' SE related to specific behaviours (e.g. pain, physical activity, coping with cancer and stress management).…”
Section: Interventi On Smentioning
confidence: 99%
See 1 more Smart Citation
“…In the area of cancer and palliative care, self-efficacy theory has been applied in symptom management for patients and for caregivers providing assistance (Given et al, 2006;Kurtz et al, 2005). Further, self-efficacy strategies, including personal mastery, vicarious experiences, verbal persuasion, and physiologic feedback, have also been applied in psychosocial interventions to help cancer patients and caregivers foster perceptions of their capacity to cope with unpredictable and stressful situations (Lee et al, 2016;Leow et al, 2015;Merluzzi et al, 2019). This framework aligns clearly with the sense of helplessness patients experience when faced with this diagnosis which is associated with poor prognosis and high disease burden.…”
Section: Introductionmentioning
confidence: 99%